Gamma Spectroscopy Prototype Design to Identify Radioactive Elements - Djokorayono, Rony; Sulaksono, Santiko Tri; Seno, Haryo; Utomo; Saptowati, Hasriyasti; Santoso, Puji; Hermana, Ferly; Wiranto BS; Sumaryanto, Agus (International Journal of Natural Science and Engineering, 2023)
The identification system for radioactive elements used the single-channel analyzer (SCA) gamma spectroscopy method. However, the process of producing the spectrum was still quite long because it had to go through the process manually by scanning its energy; one of the other radioactive elements is gamma spectroscopy. This research aims to develop a prototype gamma spectroscopy that allows the identification of radioactive elements. In this study, researchers used an experimental method by designing a gamma spectroscopy prototype consisting of a 2.5 cm diameter NaI(TL) detector equipped with a photomultiplier, high voltage module, preamp module, pulse shaping module, sample hold module, and Atmega microcontroller with an LCD display resolution of 128 × 64. The results of testing this prototype were carried out with various radioactive samples. Researchers managed to identify radioactive elements by measuring electrical pulses produced by NaI(TL) detectors. Background counting, which is the result of enumeration from detectors without radioactive material, was identified and eliminated. The distribution pattern has a random nature, the energy resolution of the spectroscopy consists of 1024 channels, and the counting time can be set as needed via the reset button. The main finding of the study was that the gamma spectroscopy prototype was able to provide a clear picture of the energy spectrum of nuclear radiation, allowing good identification of radioactive elements. The results of this study have important implications in the field of identification of radioactive elements and can be used in a variety of scientific and industrial applications involving nuclear radiation.